Analisis Penerapan Software CSMS dalam Pembuatan Invoice Penagihan Jasa Angkutan Non Semen “Klinker”: Studi Kasus PT Semen Indonesia Logistik - Alista, Meilisa Minoda; Vendy, Vicky (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze the invoice issuance procedure in the billing process for clinker transportation services using the CSMS (Customer Service Management System) at PT Semen Indonesia Logistik (SILOG). The primary focus of the research is on the workflow within the billing and reporting unit, as well as the identification of challenges and recommendations for improvement in the process. This research adopts a case study method with a qualitative approach. Data were collected through observation, interviews, and documentation. Four informants were selected using purposive sampling. The findings indicate that the billing process begins with the receipt of documents from partners, followed by document verification, data entry into the CSMS system, and invoice printing. Invoice creation is done manually so that delays often occur due to data discrepancies, input errors, incomplete documents, etc .The implications of this study reveal that despite the implementation of CSMS, technical and administrative obstacles still hinder efficiency. Improvements are needed through automated data input, integration of the contract database, and refinement of standard operating procedures (SOPs) to expedite and enhance the billing process. These findings can serve as a reference for developing a more effective digital billing system in the logistics sector.